(untitled) (Filologia e Linguística Portuguesa, 2009)
This article, which is part of the thesis Formation and expansion of the caipira dialect from Capivari written under the direction of Prof. Dr. Manoel Mourivaldo Santiago Almeida from the Universidade de São Paulo, employs a philological basis to edit 75 official folios written during the 19th century in Capivari in order to prove the fidedignity of the documents and to help the researchers in Philology who study calligraphy and abbreviations. With the aim of helping future studies, this article displays facsimilar reproductions of abbreviations.